(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this study is that it does not show the impact of measuring advertising effectiveness in ethical pharmaceutical marketing but only highlights the OTC segment. This study is that it does not show the impact of measuring advertising effectiveness in ethical pharmaceutical marketing but only highlights the measurement of brand strategy. This study is that it does not show the impact of measuring advertising effectiveness in ethical pharmaceutical marketing but only highlights the development of new products. This study is that it does not show the impact of measuring advertising effectiveness in ethical pharmaceutical marketing but only highlights the calculation of brand equity. Local, small and medium, companies dominate the Indian pharmaceutical industry with significant contribution to the national drug production and employment. They play an important role in enhancing domestic technological capabilities in drugs production and have been instrumental in keeping drugs prices affordable for the Indian populace in remote rural areas. This rise of small firms in this sector has been facilitated by a set of strategic government polices implemented in the past decades like adoption of a process patent regime, relaxation granted from price control and industrial licensing requirement, reservation of items for exclusive production and preference in government procurement, etc.